The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.2514/3.23017
|View full text |Cite
|
Sign up to set email alerts
|

Fuel thermal stability effects on spray characteristics

Abstract: The propensity of a heated hydrocarbon fuel toward solids deposition within a fuel injector is investigated experimentally. Fuel is arranged to flow through the injector at constant temperature, pressure, and flow rate and the pressure drop across the nozzle is monitored to provide an indication of the amount of deposition. After deposits have formed, the nozzle is removed from the test rig and its spray performance is compared with its performance before deposition. The spray characteristics measured include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The studies carried out by Nickolaus and Lefebvre (1987) and McCaldon et al (1993) among others, have demonstrated that coke formation within fuel nozzles can have a serious adverse effect on spray pattern. Although it has long been recognized that "cleaner" fuels of low aromatics content can greatly reduce the potential for fuel coking, this has never been regarded as a practical option due to the requirements of fuel flexibility for the military and lower-cost, heavier distillate fuels for civilian and commercial applications.…”
Section: Fuel Nozzle Cokingmentioning
confidence: 99%
“…The studies carried out by Nickolaus and Lefebvre (1987) and McCaldon et al (1993) among others, have demonstrated that coke formation within fuel nozzles can have a serious adverse effect on spray pattern. Although it has long been recognized that "cleaner" fuels of low aromatics content can greatly reduce the potential for fuel coking, this has never been regarded as a practical option due to the requirements of fuel flexibility for the military and lower-cost, heavier distillate fuels for civilian and commercial applications.…”
Section: Fuel Nozzle Cokingmentioning
confidence: 99%
“…For example, detailed measurements made with simplex, duplex, dual-orifice, and pure airblast atomizers show similar dynamic structures in radial distributions of mean droplet diameter, velocity, and liquid volume flux. Extensive studies have been made (33,34) on the spray dynamics associated with pressure swirl atomizers. Based on these studies, some common features were observed.…”
Section: Spraysmentioning
confidence: 99%
“…Using equations 9 and 10, the estimated Sauter mean diameters agree quite well with experimental data obtained for a wide range of atomizer designs. Note that the two constants in equation 11 differ from those shown in Lefebvre's equation (34). These constants have been changed to fit a wide range of experimental data.…”
Section: Spray Correlationsmentioning
confidence: 99%